1998
DOI: 10.1016/s0741-5214(98)70069-2
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia increases intimal hyperplasia in a rat carotid endarterectomy model

Abstract: This is the first study to examine IH after CEA and hyperhomocysteinemia in rats. The study shows that the elevation of serum H(e) levels can be obtained by feeding rats modified diets with added H(e). The consistent elevation of serum H(e) levels was associated with more than 4 times the amount of IH after a CEA in a rat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 28 publications
1
48
2
Order By: Relevance
“…Therefore, an elevated serum Hcy level might be partially responsible for the impaired ocular blood flow in HTCs. Southern et al (1998) reported that a Hcysupplemented diet produced elevated serum Hcy levels and subsequently increased intimal hyperplasia, with a resultant increase in luminal stenosis in a rat model. In another rat model, smoking significantly increased serum Hcy levels and luminal stenosis, and folic acid supplementation attenuated this effect (Davis et al 2004); however, none of the cases in our study was taking folic acid or smoking cigarettes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an elevated serum Hcy level might be partially responsible for the impaired ocular blood flow in HTCs. Southern et al (1998) reported that a Hcysupplemented diet produced elevated serum Hcy levels and subsequently increased intimal hyperplasia, with a resultant increase in luminal stenosis in a rat model. In another rat model, smoking significantly increased serum Hcy levels and luminal stenosis, and folic acid supplementation attenuated this effect (Davis et al 2004); however, none of the cases in our study was taking folic acid or smoking cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the general population have suggested associations between mild elevations of plasma homocysteine (Hcy) levels and coronary, cerebral, and peripheral atherosclerosis such as orbital occlusive disease (Taylor et al 1991;Wilcken 1998;Southern et al 1998;Uysal et al 2005). Increased intima media thickness (IMT) is generally considered an early marker of atherosclerosis (Erdogmus et al 2006) and causes a decrease in blood flow velocity.…”
Section: Ultrasonic Examinationmentioning
confidence: 99%
“…Dietinduced hyperhomocysteinemia is associated with vascular dysfunction in the monkey, probably due to the inhibition of nitric oxide (NO) synthesis, 1 linked with vascular structural damage in the minipig because of elastic lamina fragmentation, 2 correlated with increased postinjury intimal hyperplasia, 3 and impaired endothelial function and leukocyte-endothelium interaction in the rat. 4 A genetic hyperhomocysteinemia model with the gene deletion of cystathionine ␤-synthase (CBS), which catalyzes Hcy to cystathionine, has been used in studies of Hcy pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Morphometric analyses were performed as described previously by Southern et al [19]. In brief, after dehydration with increasing alcohol concentrations, aliquots were embedded in paraffin, and 5-lm sections from two locations 100 lm apart were prepared.…”
Section: Histomorphometrymentioning
confidence: 99%